2001
DOI: 10.1093/humrep/16.7.1365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic sperm defects and consanguinity

Abstract: From the data presented, it appears that some very peculiar and rare sperm defects may have a genetic basis since they occur more frequently in consanguineous patients, and are related to different degrees of consanguinity. Since the ejaculate of the remaining patients, both consanguineous and not, showed diverse types of ultrastructural sperm anomalies that did not affect the entire sperm population, they might represent pathologies lacking a genetic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 18 publications
4
81
0
3
Order By: Relevance
“…However, the defects they described did not involve the ICSI procedure [Kupker et al 1998]. Intacytoplasmic sperm injection excludes natural selection mechanisms and exposes the risk of transmission of genetic defects [Baccetti et al 2001, Carbone et al 1998]. Our study was designed to assess the relevance of TEM when selecting patients in which IVF would be successful.…”
Section: Resultsmentioning
confidence: 99%
“…However, the defects they described did not involve the ICSI procedure [Kupker et al 1998]. Intacytoplasmic sperm injection excludes natural selection mechanisms and exposes the risk of transmission of genetic defects [Baccetti et al 2001, Carbone et al 1998]. Our study was designed to assess the relevance of TEM when selecting patients in which IVF would be successful.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from autosomal recessive conditions which cause learning difficulties, consanguinity does not have any effect on intelligence, [85] but there is a lesser extent evidence that consanguinity affects fertility [86,87]. In contrary, other studies reported that cconsanguinity is generally associated with increased fertility, partly a result of younger maternal age at marriage.…”
Section: Genetics Considerationsmentioning
confidence: 96%
“…Baccetti et al [66] assumed that recessive autosomal mutations account for the majority of sperm genetic defects. However, the genes affected by the mutations are unknown.…”
Section: Centrosome Abnormalitiesmentioning
confidence: 99%
“…Holstein et al [68] reported a case where the basal plate and implantation fossa were normal in morphology, while separation occurred between the proximal and distal centrioles. Baccetti et al [66] described a patient with sperm ruptures occurring between the nucleus and centriole region, between the anterior and caudal regions of the mid-piece, and between the mid-piece and principal piece. A number of variants are most likely possible for sperm decapitation.…”
Section: Centrosome Abnormalitiesmentioning
confidence: 99%